Metazoan parasite fauna of conger eel Conger conger L. from Sardinian waters (Italy). - Culurgioni, Jacopo; D'Amico, Valeria; Coluccia, Elisabetta; Mulas, Antonello; Figus, Vincenza (Ittiopatologia, 2006)
Between March and May 2006, 26 specimens of conger eel Conger conger L (Osteichthyes, Congridae) caught from waters near to Sardinian coast, were examined for metazoan parasites. Twenty taxa, thirteen of which identified morphologically to the species level, were recorded. The checklist compiled after this preliminary study includes 2 ectoparasites species, the copepod Hatschekia sp. and the Polychaeta Ichthyotomus sanguinarius, and 18 endoparasites species comprising 8 digeneans, 3 cestodes, 6 nematodes and 1 acanthocephala. Most of this parasite species have been previously reported in conger eel from Mediterranean Sea except for Hatschekia sp., Proctoeces maculatus, Scolex pleuronectis and Cucullanus bioccai, new records for this host in the Mediterranean basin.
World Polychaeta Database (WPolyDb)